Professional Work and Productive Work to Improve the People's Economy: an Analysis Based on Prophetic Revelation - Budi Badrul Zaman; Muchammad Taufiq Affandi; Anass Benichou; Muthoifin (Demak Universal Journal of Islam and Sharia, 2023)
This research was conducted to analyze how to work professionally to improve the economy of the ummah based on prophetic revelations namely the Qur'an and Hadith. The method used is Library Research. The type of research used is qualitative research with a descriptive analysis approach. Data processing techniques by sorting relevant sources, classifying and compiling them systematically. The findings of this study are that work is part of worship and jihad if you follow Allah's rules consistently. The value that must be maintained at work is Itqon, which is professional which is interpreted as expert, smart, proficient, capable, accurate, careful, precise, mastery, strong, and firm. Professional indicators or itqon is always present on time and complete obligations to completion. The application of itqan values in a job includes accuracy, thoroughness, professionalism in utilizing science and technology, and consistently maintaining quality. Islam through Sharia Economics has provided concepts in work culture with several characteristics and characters including al-Shalah, al-Itqan, al-Ihsan, al-Mujahada, and Taawun.